2010
DOI: 10.5194/acp-10-6179-2010
|View full text |Cite
|
Sign up to set email alerts
|

Measured and modeled humidification factors of fresh smoke particles from biomass burning: role of inorganic constituents

Abstract: Abstract. During the 2006 FLAME study (Fire Laboratory at Missoula Experiment), laboratory burns of biomass fuels were performed to investigate the physico-chemical, optical, and hygroscopic properties of fresh biomass smoke. As part of the experiment, two nephelometers simultaneously measured dry and humidified light scattering coefficients (b sp(dry) and b sp(RH) , respectively) in order to explore the role of relative humidity (RH) on the optical properties of biomass smoke aerosols. Results from burns of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 65 publications
5
32
0
Order By: Relevance
“…It is noteworthy that more hydrophobic emissions were observed from debris compared to pine fires, probably due to production of less oxidized chemical compounds during combustion. In the small-scale study by Hand et al (2010) the scanning electron microscopy analysis revealed weak and non-hygroscopic particles, quantified by humidification factors, which were dominated by soot and organic constituents. These observations are qualitatively well in accordance with our observations of HPO and HPI particles in the C and C-O fractions.…”
Section: Fresh Smokementioning
confidence: 99%
See 4 more Smart Citations
“…It is noteworthy that more hydrophobic emissions were observed from debris compared to pine fires, probably due to production of less oxidized chemical compounds during combustion. In the small-scale study by Hand et al (2010) the scanning electron microscopy analysis revealed weak and non-hygroscopic particles, quantified by humidification factors, which were dominated by soot and organic constituents. These observations are qualitatively well in accordance with our observations of HPO and HPI particles in the C and C-O fractions.…”
Section: Fresh Smokementioning
confidence: 99%
“…In BB small-scale studies of Hand et al (2010), smoke aerosols were reported to be internally mixed and composed of inorganic salt species (KCl, K 2 SO 4 , KNO 3 , (NH 4 ) 2 SO 4 , NH 4 Cl), carbon (OC and EC), and soil (Al 2 O 3 and CaO). Therefore, the averaged characteristics of smoke hydration properties were obtained such as nonhygroscopic for ponderosa pine or more hygroscopic for sage/rabbit brush burning.…”
Section: Categorization With Respect To Hygroscopicitymentioning
confidence: 99%
See 3 more Smart Citations